Plastid genomes of the North American Rhus integrifolia-ovata complex and phylogenomic implications of inverted repeat structural evolution in Rhus L. - Craig F. Barrett (PeerJ, 2020)
Plastid genomes (plastomes) represent rich sources of information for phylogenomics, from higher-level studies to below the species level. The genus Rhus (sumac) has received a significant amount of study from phylogenetic and biogeographic perspectives, but genomic studies in this genus are lacking. Rhus integrifolia and R. ovata are two shrubby species of high ecological importance in the southwestern USA and Mexico, where they occupy coastal scrub and chaparral habitats. They hybridize frequently, representing a fascinating system in which to investigate the opposing effects of hybridization and divergent selection, yet are poorly characterized from a genomic perspective. In this study, complete plastid genomes were sequenced for one accession of R. integrifolia and one each of R. ovata from California and Arizona. Sequence variation among these three accessions was characterized, and PCR primers potentially useful in phylogeographic studies were designed. Phylogenomic analyses were conducted based on a robustly supported phylogenetic framework based on 52 complete plastomes across the order Sapindales. Repeat content, rather than the size of the inverted repeat, had a stronger relative association with total plastome length across Sapindales when analyzed with phylogenetic least squares regression. Variation at the inverted repeat boundary within Rhus was striking, resulting in major shifts and independent gene losses. Specifically, rps19 was lost independently in the R. integrifolia-ovata complex and in R. chinensis, with a further loss of rps22 and a major contraction of the inverted repeat in two accessions of the latter. Rhus represents a promising novel system to study plastome structural variation of photosynthetic angiosperms at and below the species level.